Hypothyroidism and pregnancy. Situation in Latvia - Abramova, Anna; Galsone, Ramona (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The thyroid gland is the first of the body's endocrine glands to develop, on approximately the 24th day or 3-4 weeks of gestation, but at around 10-12 weeks the thyroid begins to function on its own. Thyroid hormones are involved in regulation of vital body function. In general normal development, growth and reproduction cannot occur without them. The normal function of thyroid gland is predictor to normal pregnancy outcome and foetus development. It is important to know how many women have hypothyroidism and what kind of treatment they receive. Author selected and made retrospective analysis of women with hypothyroidism maternity cases from 2010 to 2011 year. Data compared to the control group, which includes women without hypothyroidism. 160 histories of childbirth of pregnant women with hypothyroidism were summarised and included into hypothyroidism group and 308 histories of childbirth in control group. Preeclampsia incidence in hypothyroidism group is 6.9%, and 2.6% in the control group. The incidence of preeclampsia statistically differs in both study groups. (P = 0.02642). Results of the study show that hypothyroidism does not affect the delivery type. Only 8.5% of patients in hypothyroidism group weren’t receiving L-thyroxin therapy during pregnancy. Women with hypothyroidism have preeclampsia more often than women which hasn’t hypothyroidism. Hypothyroidism does not affect the delivery type.